Analyses of competent and non‐competent subpopulations of Bacillus subtilis reveal yhfW, yhxC and ncRNAs as novel players in competence. (15th April 2020) - Boonstra, Mirjam; Schaffer, Marc; Sousa, Joana; Morawska, Luiza; Holsappel, Siger; Hildebrandt, Petra; Sappa, Praveen Kumar; Rath, Hermann; de Jong, Anne; Lalk, Michael; Mäder, Ulrike; Völker, Uwe; et al.
Summary: Upon competence‐inducing nutrient‐limited conditions, only part of the Bacillus subtilis population becomes competent. Here, we separated the two subpopulations by fluorescence‐assisted cell sorting (FACS). Using RNA‐seq, we confirmed the previously described ComK regulon. We also found for the first time significantly downregulated genes in the competent subpopulation. The downregulated genes are not under direct control by ComK but have higher levels of corresponding antisense RNAs in the competent subpopulation. During competence, cell division and replication are halted. By investigating the proteome during competence, we found higher levels of the regulators of cell division, MinD and Noc. The exonucleases SbcC and SbcD were also primarily regulated at the post‐transcriptional level. In the competent subpopulation, yhfW was newly identified as being highly upregulated. Its absence reduces the expression of comG, and has a modest, but statistically significant effect on the expression of comK . Although expression of yhfW is higher in the competent subpopulation, no ComK‐binding site is present in its promoter region. Mutants of yhfW have a small but significant defect in transformation. Metabolomic analyses revealed significant reductions in tricarboxylic acid (TCA) cycle metabolites and several amino acids in a Δ yhfW mutant. RNA‐seq analysis of Δ yhfW revealed higher expression of the NAD synthesis genes nadA, nadB and nadC .